2023
DOI: 10.3390/catal13040667
|View full text |Cite
|
Sign up to set email alerts
|

Undoped and Fe-Doped Anatase/Brookite TiO2 Mixed Phases, Obtained by a Simple Template-Free Synthesis Method: Physico-Chemical Characterization and Photocatalytic Activity towards Simazine Degradation

Abstract: For the first time, Fe-doping (0.05, 1.0, and 2.5 wt.% Fe) was performed on a high-surface-area anatase/brookite TiO2 by adopting a simple template-free sol-gel synthesis followed by calcination at a mild temperature. The powders’ textural and surface properties were characterized by following a multi-technique approach. XRD analysis showed that the anatase/brookite ratio slightly varied in the Fe-doped TiO2 (from 76.9/23.1 to 79.3/22.7); Fe doping noticeably affected the cell volume of the brookite phase, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…By comparing the samples obtained through the SCS method, the TiO 2 _SCS450 sample extended its absorption towards longer wavelengths, above 400 nm. This region could be associated with the Urbach tail, which is namely an exponential part in the energy spectrum of the absorption coefficient that may appear near the optical band edge in amorphous, disordered, and crystalline materials (Gervasi et al 2023 ). This region could be related to the presence of disorder and physisorbed water (see OH species concentration from XPS results), or was due to the higher temperature adopted during the synthesis procedure, since it was demonstrated that this parameter affects the Urbach tail (Aljishi et al 1990 ; Yap et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the samples obtained through the SCS method, the TiO 2 _SCS450 sample extended its absorption towards longer wavelengths, above 400 nm. This region could be associated with the Urbach tail, which is namely an exponential part in the energy spectrum of the absorption coefficient that may appear near the optical band edge in amorphous, disordered, and crystalline materials (Gervasi et al 2023 ). This region could be related to the presence of disorder and physisorbed water (see OH species concentration from XPS results), or was due to the higher temperature adopted during the synthesis procedure, since it was demonstrated that this parameter affects the Urbach tail (Aljishi et al 1990 ; Yap et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the catalytic properties of this oxide toward paracetamol, many studies report the possibility of introducing different heteroatoms, mainly iron (Cifci et al 2017 ; Yap et al 2020 ; de Moura et al 2021 ). This element is earth-abundant and non-toxic (Gervasi et al 2023 ) and its effect is crucial since it can be determinant for an efficient degradation (Trovó et al 2012 ). Indeed, it is well known that the presence of iron, in particular Fe 2+ , and the synergy with H 2 O 2 can enhance the mineralization of the paracetamol, mostly through the (Photo)Fenton process, which is another method belonging to AOPs.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are numerous approaches that can be used to control the phase composition of TiO 2 , including typical heat treatment, [66–68] heteroatom doping, [69–71] MOF induction, [72–74] etc. In addition, the phase transformation of TiO 2 is also affected by the reaction conditions such as pH value, reactant ratio and solvent type [75–84] …”
Section: Heterojunction Tio2 Constructed By Phase Transformationmentioning
confidence: 99%
“…The solution was magnetically stirred, the reaction temperature was kept around 20 • C, and atmospheric air was continuously bubbled inside the reactor. The solution pH was adjusted to pH = 3, 5, or 7, using HCl and NaOH solutions, and the catalyst concentration in all tests was equal to 1.0 g L −1 , similar to that reported in other works [77][78][79]. In each experiment, the catalyst used and the pH value of the solution were determined according to the experimental design (see Section 2.4).…”
Section: Photocatalytic Activity Testsmentioning
confidence: 99%